-49+f=9

Simple and best practice solution for -49+f=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49+f=9 equation:


Simplifying
-49 + f = 9

Solving
-49 + f = 9

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + f = 9 + 49

Combine like terms: -49 + 49 = 0
0 + f = 9 + 49
f = 9 + 49

Combine like terms: 9 + 49 = 58
f = 58

Simplifying
f = 58

See similar equations:

| w^2-10w+15=0 | | 2(56+24r)=-1r | | 3a-2=2a-3 | | 175-308= | | fx-gx=8 | | 5y=8y-20 | | -0.5(-2.94+3x)=-1.2x | | 39+19x=100 | | 2x^2*2x=3360 | | x(x+1)*(x+2)=3360 | | Y=9X^2+15X+52 | | 9X^2+15X+52=X | | d+2.8=9.5 | | ax+by+bx+ay= | | -2(3+m)=-3(1-m) | | 9x+4=7x+12 | | 2x+4y=200 | | 4-x^2=x^2-14 | | 8q-7=5q+11 | | 6(-2)=18 | | 4x-3-2x=9+2x-12 | | 0.5x-0.25=.92 | | 0.5x-0.25= | | 5/6(x-2)+1.3=7x/10+0.5x | | -10y=-60 | | 50s-13=55s-93 | | (2x-6)(x-4)(3x+3)=0 | | (2x-6)*(x-4)*(3x+3)=0 | | ((7-2)*3)*5= | | t^3-t-1=0 | | x-3(2x+3)=2(3-2x)-18 | | 12pq+6q= |

Equations solver categories